Managing Commonwealth Caribbean tourism for development. - Gayle, Dennis J. (1990)
Reviews the industry's economic impact during the 1980s, in terms of visitor volume and regional market shares. Examines the implicit management and market models applied within the Bahamas, Barbados and Jamaica. Reports on a survey of the experiences of visitors to the islands mentioned above, which suggests that a set of substantial structural problems remains to be resolved.